Kedudukan Mahkamah Konstitusi dalam Mewujudkan Negara Hukum yang Demokratis - Herman; Dzul Fadli; Erham (Jurnal Hukum Lex Generalis, 2026)
Debates regarding the position and role of the Constitutional Court within the Indonesian constitutional system have become a crucial issue, particularly in the effort to realize a democratic rule of law state. As the guardian of the constitution, the Constitutional Court holds strategic authority in upholding constitutional supremacy while ensuring that democratic principles are properly maintained. This study aims to analyze the position of the Constitutional Court within the Indonesian legal system and its contribution to the realization of a democratic rule of law state. The research employs a normative juridical method with statutory and conceptual approaches, supported by an analysis of Constitutional Court decisions. The results indicate that the Constitutional Court plays a central role in maintaining the constitutionality of laws, protecting the constitutional rights of citizens and controlling the exercise of power to prevent deviations from democratic principles. However, in practice, the Constitutional Court also faces various challenges, including the potential expansion of authority through constitutional interpretation and political dynamics that may affect its independence. Therefore, strengthening the position of the Constitutional Court is necessary through clarifying the limits of its authority, enhancing the integrity of constitutional judges and ensuring consistency in placing the constitution as the primary basis for all decisions. This study affirms that the Constitutional Court is a fundamental pillar in realizing a democratic rule of law state in Indonesia.